Praktik Khitan dengan Metode Sunathrone Klamp Perspektif Hukum Islam (Studi Kasus di Smart Care Center Makassar) - Rachmat Bin Badani Tempo; Sarni, Santi; Sri Ujiana Putri; Fadhilah, Nur (BUSTANUL FUQAHA: Jurnal Bidang Hukum Islam, 2021)
This study aimed to examine the practice of circumcision using the Sunathrone Klamp method at the Makassar Smart Care Center Clinic in a review of Islamic law. This research used field research using normative theological approaches and health approaches. Data collection techniques were conducted through observation, interviews, and documentation. The research results found; 1) The healing process of the circumcision wound has a phase in 3 weeks (21 days), in which the skin will return to its original shape. There are three phases of wound healing after circumcision using the Sunathrone Klamp method, namely the inflammation phase, the proliferation phase, and the remodeling phase; 2) The advantages of the Sunathrone Klamp include a relatively short time, no stitches, minimizing pain, psychologically the child feels comfortable when circumcised, and relatively fast healing time. The drawbacks after circumcision are that the patient feels uncomfortable because the clamp will be installed in a few days, and has a high level of operational standards, so that it is only used by experts in the field; and 3) Sunathrone Klamp is a practical tool for circumcision or circumcision with an easier, safer, and hygienic working process. In a review of Islamic law, the Sunathrone Klamp method is permissible, as long as the circumcision process is carried out by an expert or professional.